The use of metronidazole in women undergoing obstetric anal sphincter injuries: a systematic review of the literature - Rotem, Reut; Mastrolia, Salvatore Andrea; Rottenstreich, Misgav; Yohay, David; Weintraub, Adi Y. (Archives of gynecology and obstetrics, 2020)
Purpose Antibiotic treatment during surgical repair of obstetric anal sphincter injuries (OASIS) had been a matter of debate. We aimed to review the available literature regarding the efficacy of metronidazole administration in women undergoing perineal repair following obstetric OASIS. Study design To identify potentially eligible studies, we searched PubMed, Scopus, Embase and the Cochrane Library from inception to January 13th, 2019.Reference lists of identified studies were searched. No language restrictions were applied. We used a combination of keywords and text words represented by “Metronidazole”, “obstetrics”, “obstetric anal sphincter injury”, “OASIS”, “third degree tear”, “fourth degree tear”, “third degree laceration”, “fourth degree laceration”, “antibiotic therapy”, “perineal damage” and “perineal trauma”. Two reviewers independently screened the titles and abstracts of records retrieved from the database searches. Both reviewers recommended studies for the full-text review. Thescreen of full-text articles recommended by at least one reviewer was done independently by the same two reviewers and assessedfor inclusion in the systematic review. Disagreements between reviewers were resolved by consensus. Results The electronic database search yielded a total of 54,356 results (Fig. 1 ). After duplicate exclusion 28,154 references remained. Of them, 26 were relevant to the review based on title and abstract screening. None of these articles dealt with the use of metronidazole for the prevention of infections complicating anal sphincter repair in women with OASIS. A Cochrane review addressing antibiotic prophylaxis for patients following OASIS, compared prophylactic antibiotics against placebo or no antibiotics, included only one randomized controlled trial of 147 participants. This study showed that prophylactic antibiotics (not metronidazole) may be helpful to prevent perineal wound complications following OASIS. Fig. 1 Study seection process Conclusion Anaerobic infections potentially complicate wound repair after OASIS. Although scientific societies recommend the use of antibiotics for the prevention of infectious morbidity after OASIS, no study has specifically assessed the role of metronidazole.